PENINGKATAN KESADARAN LINGKUNGAN MELALUI EDUKASI SAMPAH DAN PENGGUNAAN TOTE BAG BERKELANJUTAN DI WISATA KAMPUNG SEGA KELURAHAN MENDAWAI - Tirtayano, Anandha Destyarennie; Andrian, Freny; Syafadilla , Elva; Arifin, Gusti Muhammad Bustanil; Kasmiah , Utin Nur; Hanifah, Hanifah; Nisa , Kherun; Hakim , Sofyan (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
This community service activity was carried out by students of KKN group 75 at Kampung Sega Tourism Site, Mendawai Village, with the aim of increasing environmental awareness through education about waste and the use of sustainable tote bags. The program focused on installing educational signs about the decomposition time of waste, which took place from July 18 to August 25, 2024. The method used included preparation, implementation, and evaluation stages. This activity not only involved the installation of signs but also the distribution of tote bags and water bottles as eco-friendly alternatives. Evaluation results showed an increase in community understanding of the impact of waste and the importance of proper management, although further efforts are still needed to change daily behavior. This program represents a concrete step in addressing the plastic waste problem and is expected to have a long-term positive impact on the environment and local community.